Basics of contemporary cryptography for IT practitioners - Ryabko, Boris (Series on coding theory and cryptology, 2005)
The aim of this book is to provide a comprehensive introduction to cryptography without using complex mathematical constructions. The themes are conveyed in a form that only requires a basic knowledge of mathematics, but the methods are described in sufficient detail to enable their computer implementation. The book describes the main techniques and facilities of contemporary cryptography, proving key results along the way. The contents of the first five chapters can be used for one-semester course.